Does Crop Insurance Influence Commercial Crop Farm Decisions to Expand? An Analysis Using Panel Data from the Census of Agriculture - Christopher B. Burns; Daniel L. Prager (Journal of Agricultural and Resource Economics, 2018)
The Agricultural Act of 2014 increased the role of risk-mitigating policies in U.S. agricultural policy and focused attention on how crop insurance affects farm production decisions. Using detailed farm-level data from the Census of Agriculture and supplemental county-level data, this paper seeks to understand whether purchasing crop insurance influences commercial crop farms' decisions to expand. After instrumenting for the endogenous decision to purchase crop insurance, we find that paying higher net premiums had no statistically significant effect on crop farm expansion from 2007 to 2012. We also find that farms expanded more when they were located in counties with more acres enrolled in the Conservation Reserve Program.